Nutraceuticals in the Modulation of the Intestinal Microbiota: Current Status and Future Directions - Spisni, Enzo; Turroni, Silvia; Alvisi, Patrizia; Spigarelli, Renato; Azzinnari, Demetrio; Ayala, Dario; Imbesi, Veronica; Valerii, Maria Chiara (Frontiers in Pharmacology, 2022)
Pharmaceutical interest in the human intestinal microbiota has increased considerably, because of the increasing number of studies linking the human intestinal microbial ecology to an increasing number of non-communicable diseases. Many efforts at modulating the gut microbiota have been made using probiotics, prebiotics and recently postbiotics. However, there are other, still little-explored opportunities from a pharmaceutical point of view, which appear promising to obtain modifications of the microbiota structure and functions. This review summarizes all in vitro, in vivo and clinical studies demonstrating the possibility to positively modulate the intestinal microbiota by using probiotics, prebiotics, postbiotics, essential oils, fungus and officinal plants. For the future, clinical studies investigating the ability to impact the intestinal microbiota especially by using officinal and aromatic plants or their extracts are required. This knowledge could lead to effective microbiome modulations that might support the pharmacological therapy of most non-communicable diseases in a near future.